Under the Sign of Kandinsky. On Pure Becoming in the Poetics of the Maldonado Bailey Brothers - Del Gizzo, Luciana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The work of Tomás Maldonado (1922), painter and designer, and Edgar Bayley (1919-1990), poet, share the features of simplicity, sobriety, and accuracy. But their blood relation is not enough to explain that “family air” that binds their productions. Their different artistic disciplines blurs the comparison of these features in their work. This study starts from the concept of «purity of forms», present in the develop - ment of abstract art and modern poetry, and the comparative analysis of the theoretical productions of both artists, and inquires about mutual influences and joint reflections which led them to agree on and elaborate a consolidated avant-garde discourse, which ended up linking their productions